(untitled) (Journal of Universal Science Research, 2025)
Shakespeare’s tragedies stand as masterpieces of world literature, distinguished by their profound psychological depth, complex character portrayals, and sophisticated stylistic devices. His use of poetic language, metaphor, rhetorical devices, and archaic expressions presents significant challenges for translators, particularly when adapting his works into Uzbek. This article examines the key stylistic features of Shakespeare’s tragedies, such as Hamlet, Othello, Macbeth, and King Lear, and analyzes how they are rendered in Uzbek translations. The study highlights the strategies employed by Uzbek translators to balance linguistic fidelity and cultural adaptation, ensuring that the essence of Shakespeare’s works is preserved.